Effects of caffeine on prolonged intermittent-sprint ability in team-sport athletes - Schneiker, K. T.; Bishop, D.; Dawson, B.; Hackett, L. P. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Caffeine can be a powerful ergogenic aid for the performance of prolonged, submaximal exercise. Little evidence, however, supports an ergogenic effect of caffeine on intermittent-sprint performance. Hence, this study was conducted to examine the effects of acute caffeine ingestion on prolonged intermittent-sprint performance.